Targeted BRAF /MEK inhibition as a salvage therapy for patients with metastatic melanoma harboring a BRAF L597R mutation: two case reports and review of the literature - Andrew Moufarrej; Sarah Biermann; Robin Springer; Norman-Philipp Hoff; Bernhard Homey; Harm-Henning Lindhof (Melanoma Research, 2026)
Combined B-Raf proto-oncogene, serine/threonine kinase/MAPK kinase (BRAF/MEK) inhibition, along with immune checkpoint inhibition, has significantly improved the outcomes of patients with advanced melanoma harboring BRAF V600 mutations. However, the clinical efficacy of targeted therapy for melanomas with rare class II BRAF mutations, such as L597R, remains unclear. We report two patients with metastatic BRAF L597R-mutated melanoma who responded to BRAF/MEK inhibition. Both patients initially underwent dual immune checkpoint inhibition. Because of rapid clinical deterioration and disease progression, the treatment was switched to binimetinib in case 1 and binimetinib/encorafenib combination therapy in case 2. Both patients demonstrated a rapid clinical response to targeted therapy, including a notable reduction in the tumor burden and symptomatic improvement. In case 1, resistance developed after 3 months, resulting in disease progression. In case 2, targeted therapy was discontinued after 8 weeks because of the anticipated emergence of resistance, and immune checkpoint inhibition was reinitiated. Stable disease and symptom control were maintained for an additional 6 months, after which disease progression was observed. The overall survival rates were 10 and 11 months, respectively. These cases illustrate that targeted therapy can induce a rapid response in patients with metastatic melanoma harboring the BRAF L597R mutation while also highlighting the risk of early treatment resistance. This treatment option should be considered, particularly for patients with pronounced symptoms and high tumor burden.